The Influence of Brand Image, Price, Quality on Compulsive Buying Disorder of Imported Used Clothing Among Generation Z in the Perspective of Sharia Economics - Chuzaimah Batubara; Inayatul Widad Nasution (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This study aims to analyze price, quality, and brand image on compulsive buying disorder because fast-changing fashion trends among consumers tend to make consumers become exaggerated and use various ways to follow trends, especially buying imported used clothes. Formulation of the problem is What is the phenomenon of Generation Z in choosing to buy imported used clothing, what are the causes of Generation Z committing compulsive buying disorder in choosing imported used clothing, Does imported used clothing have a positive or negative effect on the survival of Generation Z. While the purpose of the research is to answer the problem formulated above. This research method is associative quantitative. The population in this study is Generation Z who are in the UIN North Sumatra environment, namely Islamic Economics Students in 2022 totaling 100 students. The analytical method used is Moderated Regression Analysis (MRA) with the SPSS 25 application and the results are obtained: The t-test results for the variable X1 t count are less t table (1.164 <1.984.), and a significance value is 0.247> 0.05. The results of the t-test for the price variable mean that individually the price does not have a significant effect on compulsive buying disorder. X2 The value of tcount exceeds ttable (-0.755 > 1.984.), and a significance value of 0.452 > 0.05. shows that product quality does not affect compulsive buying disorder behavior. X3 Individual Brand Image has a significant effect on compulsive buying disorder. The t count value exceeds t table (78.410 > 1.984.), and a significance value of 0.000 <0.05.